WHOLE LIFE INSURANCE UTILIZING THE COMMISSIONERS METHOD AND THE VASICEK INTEREST RATE MODEL FOR PREMIUM RESERVE ANALYSIS - Krishna Prafidya Romantica; Arsyelina Husni Johan; Anuraga Jayanegara; Jason Filbert Leo (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2026)
Premium reserves play a vital role in ensuring that insurance firms can meet their future obligations to policyholders. Traditional fixed-rate approaches often fail to reflect market volatility, leading to potential misestimations. This study addresses this gap by integrating the Commissioners Method with the Vasicek stochastic interest rate model to evaluate premium reserves for whole life insurance. The research hypothesizes that the Vasicek model provides more realistic reserve estimates than fixed-rate models, that payment frequency and behavioral preferences significantly affect reserve levels, and that gender-specific mortality impacts reserve adequacy. Using BI-7D-RR interest rate data from 2019–2024, Vasicek parameters were calibrated and applied to reserve calculations. A sensitivity analysis was conducted by varying the model’s mean reversion, volatility, and long-term mean parameters. The results confirm that Vasicek-based reserves are more robust and realistic than fixed-rate estimates. Incorporating a DARA utility function adds behavioral realism, while payment frequency strongly influences reserve accumulation. Gender-specific mortality produces systematically higher reserves for male policyholders. Sensitivity analysis highlights the model’s robustness, with reserves responding predictably to parameter changes. This research contributes theoretically by linking stochastic modeling, demographics, and behavioral economics, while providing practical guidance for insurers to strengthen reserve adequacy and financial resilience under uncertainty.